2016
DOI: 10.1088/1748-6041/11/2/025022
|View full text |Cite
|
Sign up to set email alerts
|

Local release from affinity-based polymers increases urethral concentration of the stem cell chemokine CCL7 in rats

Abstract: The protein chemokine (C-C motif) ligand 7 (CCL7) is significantly over-expressed in urethral and vaginal tissues immediately following vaginal distention in a rat model of stress urinary incontinence. Further evidence, in this scenario and other clinical scenarios, indicates CCL7 stimulates stem cell homing for regenerative repair. This CCL7 gradient is likely absent or compromised in the natural repair process of women who continue to suffer from SUI into advanced age. We evaluated the feasibility of locally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…We herein used both in silico and in vitro measurements to predict and confirm the relative affinity of the selected drugs for β-CD or the base polymer without inclusion complex formation, dextran (Figures 1 and 2). Previous studies have demonstrated using cyclodextrin monomers polymerized into larger macrostructures such as coatings, disks, and particles in order to delay drug release by achieving a high concentration of affinity-binding sites [27,30,31,37,44,45]. The release results herein show differences in the loading efficiencies (Figure 3), release rates ( Figure 4), and cumulative amounts of drug release ( Figure 5) which may inform the future use and design of local drug delivery depots.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…We herein used both in silico and in vitro measurements to predict and confirm the relative affinity of the selected drugs for β-CD or the base polymer without inclusion complex formation, dextran (Figures 1 and 2). Previous studies have demonstrated using cyclodextrin monomers polymerized into larger macrostructures such as coatings, disks, and particles in order to delay drug release by achieving a high concentration of affinity-binding sites [27,30,31,37,44,45]. The release results herein show differences in the loading efficiencies (Figure 3), release rates ( Figure 4), and cumulative amounts of drug release ( Figure 5) which may inform the future use and design of local drug delivery depots.…”
Section: Discussionmentioning
confidence: 83%
“…β-CD was used as a host for small molecule docking in PyRx (Molecular Graphics Laboratory, The Scripps Research Institute, La Jolla, CA, USA). The strength of the interaction was predicted using the Autodock Vina algorithm [26][27][28][29].…”
Section: Molecular Docking Simulationsmentioning
confidence: 99%
“…Reliable and durable low cost animal model may help in testing promising novel regenerative treatments for SUI . The success to create a reliable VD mouse model may help explore the individualized genetic variabilities and possible novel microenviromental manuvers in the treatment of SUI patients …”
Section: Discussionmentioning
confidence: 99%
“…20,21 The success to create a reliable VD mouse model may help explore the individualized genetic variabilities and possible novel microenviromental manuvers in the treatment of SUI patients. 22 This is the highest powered rodent study using the VD model of simulated birth trauma to date. In the previous studies, 1-h VD with 0.3 mL resulted in demonstrable SUI that exhbits a pattern of nadir in LPP at 4 days and a recovery over the course of 20 days.…”
Section: Discussionmentioning
confidence: 99%
“…pCD hydrogels have previously shown to successfully deliver small-molecule drugs on the scale of a few weeks leveraging thermodynamic interactions, or 'affinity', between hydrophobic molecules and cyclodextrin's hydrophobic complexation domain, or "pocket" [10,11,12,13,14]. pCD networks can be made into large macrostructures including disks and particles, which have been shown to load relatively high amounts of drugs while altering the window of release, resulting in an extended 'affinity-based' release rather than a purely diffusion-based release [15,16]. This system produced a 28-day window of release, which satisfies the time frame for wound healing but not for many other applications like immunosuppression [9].…”
Section: Introductionmentioning
confidence: 99%